ANALISIS PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Penjualan di PT. Perindustrian Bapak Djenggot Bergas, Semarang) - Hanantoko, Destu Aji; Nugraheni, Rini (Diponegoro Journal of Management, 2017)
Human Resources is one factor that is vital as a determinant of the success of the company. The Company's success itself is usually determined from the performance of its employees. From the results of the pre-survey known phenomenon that occurs in the company is a decrease in employee performance. On the other hand the discovery of Research Gap from previous studies on the influence of work motivation, leadership and organizational  culture  on  employee  performance.  This  is  the  background  to  do  the research.This study uses the work motivation, leadership and organizational culture as an independent  variable,  and  employee  performance  as  the  dependent  variable.  The population of this research is a sales employee of PT. Industry Mr. Djenggot Bergas Semarang. The sampling technique used is sampling saturated, with a sample of 64 people. The data obtained has been tested reliability and invalidity using validity and reliability. The method used in this research is multiple linear regression analysis.Based on the results of multiple linear regression analysis showed that there is a positive  and  significant  influence  of  work  motivation,  leadership  and  organizational culture  on  employee  performance.  Of  the  coefficient  of  determination  shows  that motivation, leadership and organizational culture influence on employee performance of sales PT. Industry Mr. Djenggot Bergas Semarang 23.4%. While the remaining 76.6% is explained by other variables that are not described in this study.